Fluororubber compound for injection molding and method for preparing the same
Patent Information
- Application Number
- CN202611224345.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0008]针对现有注射成型用氟橡胶混炼胶制备过程中加料节点难以适应胶料实际混炼状态,容易造成不同门尼黏度氟橡胶融合不足、填料分散不均以及批次稳定性较差的问题,本发明提供一种注射成型用氟橡胶混炼胶及其制备方法,能够提高混炼过程的可控性,促进不同门尼黏度氟橡胶充分融合和填料均匀分散,使所得混炼胶具有良好的注射成型加工性能和稳定的硫化后性能
[0020]相比于现有技术,本发明通过对不同门尼黏度氟橡胶的加入顺序及混炼状态进行协同控制,使低门尼黏度的第一氟橡胶先行塑化并形成连续载体,促进吸酸剂和填料的初步润湿与包覆,再以第一扭矩峰值T1为基准,根据扭矩比T/T1与胶料温度共同确定高门尼黏度第二氟橡胶的加入时点,从而使第二氟橡胶在适宜的混炼负载和热状态下逐步分散并与第一氟橡胶充分融合,降低固定时间或单一温度控制容易受到原料温度、设备热状态及批次差异影响的问题。在此基础上,通过白炭黑分批加入维持有效剪切,并抑制瞬时混炼负载升高和温升过快,通过延后加入氟蜡、巴西棕榈蜡和聚乙烯蜡,使前段填料分散与后段流动调节相互衔接;母炼胶冷却后在较低温度下依次加入双酚AF和苄基三苯基氯化鏻,有利于硫化组分均匀分布并降低局部提前反应的风险。上述工艺环节依次衔接,使不同黏度氟橡胶的融合、填料分散、混炼热历程和硫化体系分布得到整体调控,在提高混炼胶注射流动性和模腔填充稳定性的同时,兼顾焦烧安全性、硫化均匀性、力学性能及压缩永久变形性能,并能够根据初始热状态的变化调整第二氟橡胶生胶的加入时点,减小由此引起的注射流动性能波动,体现出各控制步骤协同产生的综合技术效果。
Smart Images

Figure CN122878693A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fluororubber processing technology, and more specifically, relates to a fluororubber compound for injection molding and its preparation method. Background Technology
[0002] Fluororubber is a type of synthetic polymer elastomer containing fluorine atoms in its molecular structure. It possesses good high-temperature resistance, oil resistance, chemical resistance, aging resistance, and sealing performance, and is widely used in the automotive, aerospace, petrochemical, and machinery industries. It can be used to manufacture oil seals, O-rings, gaskets, diaphragms, and other media-resistant sealing products. Before molding fluororubber products, raw fluororubber is typically mixed with acid scavengers, reinforcing fillers, processing aids, vulcanizing agents, and vulcanization accelerators to form a fluororubber compound with corresponding processing and vulcanization properties. The dispersion state and rheological properties of the components in the compound directly affect the subsequent molding process and the performance of the finished product.
[0003] Fluororubber products can be processed using compression molding, extrusion molding, or injection molding. Injection molding offers advantages such as easy automatic control of metering and feeding, faster mold filling speed, and suitability for processing complex products. However, it places higher demands on the flowability, scorch safety, vulcanization characteristics, and batch stability of the rubber compound. Insufficient flowability of the rubber compound can lead to unstable feeding, incomplete mold filling, or localized missing rubber. Insufficient scorch safety during shearing and heating can cause premature vulcanization, affecting the flowability of the rubber compound and mold filling. Excessively reducing the viscosity of the rubber compound may weaken its stiffness, reinforcing effect, and post-vulcanization mechanical properties. Therefore, fluororubber compounds for injection molding need to achieve a reasonable balance between processing flowability, scorch safety, filler dispersibility, and post-vulcanization performance.
[0004] Existing technologies have proposed improving the processing properties of fluororubber compounds by selecting fluororubber raw materials with different Mooney viscosities and adding processing aids. For example, Chinese patent application CN104356559A discloses a fluororubber compound and its preparation method, which uses fluororubber raw materials with a Mooney viscosity of 50 and 20, and adds components such as activated magnesium oxide, calcium hydroxide, fluorowax, release agent, carnauba wax, spray-dried carbon black, bisphenol AF, and vulcanization accelerator BPP. This method involves adding the raw materials to a mixer for stirring and mixing, followed by cooling, thin-passing, and open-milling treatments to improve the flowability and hot tear resistance of the compound. This technology has studied the application of fluororubbers with different Mooney viscosities, but the mixing process is mainly controlled according to preset stirring time, temperature, pressure, and speed. After the raw materials are added together, the fusion state of the raw materials with different viscosities and the dispersion state of the fillers still mainly depend on the fixed process parameters.
[0005] Chinese patent application CN102875937A discloses a fluororubber compound and its preparation method. It employs a reinforcing system composed of binary low-to-medium Mooney fluororubber, N990 carbon black, and inorganic fillers; an acid-absorbing system composed of active magnesium oxide and calcium hydroxide; and a vulcanization system composed of bisphenol AF and a vulcanization accelerator. A release agent and an auxiliary vulcanizing agent are also added. The preparation process includes open milling and plasticizing, premixing of the vulcanization system, resting, adding reinforcing fillers and other additives, and repeated thin-pass mixing, resulting in a compound with good flowability, scorch safety, and mechanical properties. This method mainly relies on formula adjustment, auxiliary vulcanizing agents, and multiple thin-pass mixing and resting processes to improve the compound's properties. The process cycle is relatively long, and there is a lack of direct process criteria for judging the actual viscoelastic state changes of the compound during the internal mixing process.
[0006] During the internal mixing process, fluororubber raw rubber is subjected to continuous compression, shearing, and heating. Raw rubbers with different Mooney viscosities exhibit differences in plasticizing rate, shear response, and filler coating ability. The addition of reinforcing fillers can also cause significant changes in compound viscosity and mixing torque. When raw material batches, equipment loading conditions, cooling conditions, and ambient temperature fluctuate, using only fixed mixing time or temperature as a control basis may result in different batches of rubber being in different actual mixing states, leading to inconsistencies in filler dispersion, processing fluidity, and vulcanization performance.
[0007] Therefore, existing fluororubber compounds and their preparation technologies still need to further address the issue of stable fusion of fluororubbers of different viscosities during the mixing process, and improve the dispersion uniformity of reinforcing fillers and the controllability of the mixing process, so that the resulting compound can maintain mechanical and sealing properties while possessing flowability suitable for injection molding, scorch safety, and batch stability. Summary of the Invention
[0008] To address the problems of insufficient fusion of fluororubber compounds with different Mooney viscosities, uneven filler dispersion, and poor batch stability in the preparation of existing fluororubber compounds for injection molding, which are difficult to adapt to the actual mixing state of the rubber compound, this invention provides a fluororubber compound for injection molding and its preparation method. This method can improve the controllability of the mixing process, promote the full fusion of fluororubbers with different Mooney viscosities and the uniform dispersion of fillers, and give the resulting compound good injection molding processing performance and stable post-vulcanization properties.
[0009] To solve the above problems, the present invention adopts the following technical solution.
[0010] A method for preparing a fluororubber compound for injection molding includes the following steps: (1) Pre-cool the mixing chamber of the internal mixer to below 70°C, put the raw rubber of the first fluororubber into the internal mixer for plasticizing, and then add active magnesium oxide, calcium hydroxide, N990 carbon black, calcium silicate and barium sulfate for mixing; (2) After the above components are fed and the top bolt is closed, the mixing torque is recorded after the pressure of the top bolt reaches the set value. The first peak torque recorded is recorded as T1. During the torque drop phase after T1, when the ratio of the real-time torque T to T1 is 0.85 to 0.93 and the rubber temperature is 90 to 105°C, the second fluororubber raw rubber is added and mixing continues. From the start of recording the mixing torque until the addition of the second fluororubber raw rubber, the rotor speed setting value and the top bolt pressure setting value of the internal mixer remain unchanged. (3) After the second batch of fluororubber raw rubber is added and mixed, silica is added in two batches. After the first batch of silica is added and mixed, the second batch of silica is added. (4) After the second batch of silica is added and mixed, fluorinated wax and carnauba wax are added; when the temperature of the rubber compound reaches 105-115℃, polyethylene wax is added, and mixing continues. When the temperature of the rubber compound reaches 115-125℃, the rubber is discharged to obtain the masterbatch. (5) The masterbatch is sheeted and cooled to below 40°C, and then placed in a two-roll mill. Bisphenol AF and benzyltriphenylphosphonium chloride are added sequentially under the condition that the roller temperature of the two-roll mill is 35-50°C and the temperature of the rubber compound is not higher than 60°C. After mixing and sheeting, fluororubber compound for injection molding is obtained. Both the first and second fluororubber raw rubbers are suitable for bisphenol vulcanization systems. The Mooney viscosity of the first fluororubber raw rubber is 20-30, and the Mooney viscosity of the second fluororubber raw rubber is 65-75. The Mooney viscosity of both is expressed in ML(1+10)121℃.
[0011] Preferably, based on a total of 100 parts by weight of the first fluororubber raw material and the second fluororubber raw material, the amounts of each component are as follows: The mixture consists of 78-82 parts by weight of first-grade fluororubber raw rubber, 18-22 parts by weight of second-grade fluororubber raw rubber, 6 parts by weight of activated magnesium oxide, 6 parts by weight of calcium hydroxide, 20 parts by weight of N990 carbon black, 10 parts by weight of calcium silicate, 5 parts by weight of barium sulfate, 10 parts by weight of silica, 1 part by weight of fluorinated wax, 1.5 parts by weight of carnauba wax, 0.8 parts by weight of polyethylene wax, 2.17 parts by weight of bisphenol AF, and 0.5 parts by weight of benzyltriphenylphosphonium chloride.
[0012] Preferably, neither the first fluororubber raw rubber nor the second fluororubber raw rubber is premixed with bisphenol AF and benzyltriphenylphosphonium chloride before being fed into the internal mixer.
[0013] Preferably, when the second fluororubber raw rubber is added, the ratio of the real-time torque T to T1 is 0.88 to 0.91, and the rubber compound temperature is 94 to 100°C.
[0014] Preferably, the plasticizing time of the first fluororubber raw rubber is 60-90s; after the second fluororubber raw rubber is added, continue mixing for 60-120s, and then add the first batch of silica.
[0015] Preferably, the first batch of silica accounts for 55% to 70% of the total silica usage, and the second batch of silica is the remainder; after the first batch of silica is added, continue mixing for 30 to 60 seconds before adding the second batch of silica.
[0016] Preferably, after the second batch of silica is added, continue mixing for 30-60 seconds, then add fluorowax and carnauba wax; after the polyethylene wax is added, continue mixing for 30-60 seconds, and discharge the rubber compound when the temperature reaches 115-125℃.
[0017] Preferably, after adding bisphenol AF and benzyltriphenylphosphonium chloride, the adhesive is passed through a thin tube 5 to 6 times and then sheeted out.
[0018] Preferably, the fluororubber compound for injection molding after sheeting is sealed and left to stand at 20-30°C for 16-24 hours.
[0019] A fluororubber compound for injection molding, based on a total of 100 parts by weight of first fluororubber raw material and second fluororubber raw material, comprises the following raw materials: The mixture consists of 78-82 parts by weight of first-grade fluororubber raw rubber, 18-22 parts by weight of second-grade fluororubber raw rubber, 6 parts by weight of activated magnesium oxide, 6 parts by weight of calcium hydroxide, 20 parts by weight of N990 carbon black, 10 parts by weight of calcium silicate, 5 parts by weight of barium sulfate, 10 parts by weight of silica, 1 part by weight of fluorinated wax, 1.5 parts by weight of carnauba wax, 0.8 parts by weight of polyethylene wax, 2.17 parts by weight of bisphenol AF, and 0.5 parts by weight of benzyltriphenylphosphonium chloride. Both the first and second fluororubber raw rubbers are suitable for bisphenol vulcanization systems. The Mooney viscosity of the first fluororubber raw rubber is 20-30, and the Mooney viscosity of the second fluororubber raw rubber is 65-75. The Mooney viscosity of both is expressed in ML(1+10)121℃.
[0020] Compared to existing technologies, this invention achieves superior results by synergistically controlling the addition sequence and mixing state of fluororubbers with different Mooney viscosities. This allows the first fluororubber with low Mooney viscosity to be plasticized first, forming a continuous carrier and promoting the initial wetting and coating of acid scavengers and fillers. Then, using the first torque peak T1 as a benchmark, the addition time of the second fluororubber with high Mooney viscosity is determined based on the torque ratio T / T1 and the compound temperature. This ensures that the second fluororubber gradually disperses and fully integrates with the first fluororubber under suitable mixing load and thermal conditions, reducing the susceptibility of fixed-time or single-temperature control to variations in raw material temperature, equipment thermal state, and batch differences. Furthermore, the phased addition of silica maintains effective shear and suppresses rapid increases in instantaneous mixing load and temperature rise. The delayed addition of fluorowax, carnauba wax, and polyethylene wax ensures seamless integration between the initial filler dispersion and subsequent flow regulation. Finally, the sequential addition of bisphenol AF and benzyltriphenylphosphonium chloride at a lower temperature after cooling the masterbatch promotes uniform distribution of vulcanizing components and reduces the risk of premature local reactions. The above-mentioned process steps are sequentially connected, which enables the overall control of the fusion of fluororubbers of different viscosities, filler dispersion, mixing thermal history, and vulcanization system distribution. While improving the injection flowability and mold cavity filling stability of the compound, it also takes into account scorch safety, vulcanization uniformity, mechanical properties, and compression set performance. Furthermore, it can adjust the timing of adding the second fluororubber raw material according to changes in the initial thermal state, reducing the resulting fluctuations in injection flow performance, and demonstrating the comprehensive technical effect produced by the synergy of each control step. Attached Figure Description
[0021] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation
[0022] The present invention will be further illustrated below through specific embodiments. Unless otherwise specified, all raw materials used in the embodiments are commercially available industrial products, and operations not specifically described can be performed using conventional methods in the art.
[0023] This invention employs two types of fluororubber raw materials with different Mooney viscosities, and completes the mixing process in the following sequence: initial wetting, state-triggered addition of the second fluororubber raw material, subsequent reinforcement, and low-temperature vulcanization. Each stage is interconnected: the first fluororubber raw material initially carries the initial filler; the degree of torque peak decline and the compound temperature jointly determine the timing of the addition of the second fluororubber raw material. The re-established mixing load after the addition of the second fluororubber raw material continues to be used for silica dispersion. Waxes and the vulcanization system are added after filler dispersion and under low-temperature conditions, respectively. The following details this process in conjunction with raw materials, equipment, and examples.
[0024] The examples used two types of vinylidene fluoride / hexafluoropropylene binary copolymer raw rubbers. Both have the same monomer system and are suitable for bisphenol vulcanization systems; the main difference lies in their Mooney viscosity. The Mooney viscosity of the first fluororubber raw rubber is 20–30, and that of the second fluororubber raw rubber is 65–75, both measured using ML(1+10) at 121°C. Neither type of raw rubber was pre-mixed with bisphenol AF and benzyltriphenylphosphonium chloride before being fed into the internal mixer. Other embodiments may also use binary or ternary fluororubbers that meet the above vulcanization system and Mooney viscosity requirements.
[0025] Activated magnesium oxide and calcium hydroxide are used for activation and acid absorption in the bisphenol vulcanization system. N990 carbon black, calcium silicate, barium sulfate, and silica together constitute the filler and reinforcing system. N990 carbon black, calcium silicate, and barium sulfate are added in the initial stages, while silica is added in batches after the two raw rubbers are mixed. Fluoropolymer wax, carnauba wax, and polyethylene wax are used to adjust the flow and release properties in the later stages. The example uses polyethylene wax with a softening point of 105–115°C, allowing it to soften quickly and enter the rubber compound at the specified addition temperature.
[0026] The embodiment uses a tangential rotor internal mixer capable of online acquisition of top plug pressure, rotor torque, and rubber compound temperature, with a loading factor of 0.68–0.72. After the front-end filler is fed and the top plug is closed, torque recording begins when the actual pressure reaches ±5% of the set value and remains there for 3 seconds. The torque sampling frequency is 5Hz, and the acquired signal is processed using a 2-second moving average. The first local maximum value appearing on the processed curve is recorded as T1. Real-time torque T and T1 are obtained from the same sensor in the same manner. From the start of recording until the addition of the second fluororubber raw rubber, the rotor speed setpoint and top plug pressure setpoint remain unchanged; normal fluctuations within the equipment control accuracy are not considered changes to the setpoints.
[0027] T / T1 reflects the decline in the mixing load of this batch relative to the previous peak value. Using this ratio can reduce the influence of equipment range, loading status, and initial differences in raw rubber on absolute torque. This ratio still varies with compound temperature and thermal softening; conversely, an increase in temperature does not alone indicate that the upstream filler has reached the corresponding wetting and dispersion process. Therefore, this invention uses T / T1 to characterize the relative load change, uses compound temperature to define the thermal state, and uses the intersection of these two conditions as the addition window for the second fluororubber raw rubber. When one of these conditions first enters the specified range, mixing continues until both conditions are met simultaneously for the first time.
[0028] At the start of preparation, the mixing chamber of the internal mixer is pre-cooled to below 70°C. First, raw fluororubber is added and masticated for 60–90 seconds. Then, activated magnesium oxide, calcium hydroxide, N990 carbon black, calcium silicate, and barium sulfate are added. Pre-cooling allows for temperature rise during subsequent mechanical heating, ensuring that the initial mixing is carried out before the rubber compound becomes excessively softened. The raw fluororubber has a low Mooney viscosity, making it easier to spread and penetrate between powder particles after mastication. Therefore, it can first coat the front-end fillers, expel air from between agglomerates, and form a front-end filler dispersion carried by the raw fluororubber.
[0029] After the top bolt is closed, the compacted powder, rubber-coated powder, and agglomerates enter the shear zone, jointly driving the torque increase, forming T1. As the front filler is gradually wetted and the first fluororubber raw rubber continues to plasticize, the torque drops from its peak. When T / T1 is 0.85–0.93 and the rubber compound temperature is 90–105°C, it corresponds to a transition range where the front filler has completed its main compaction and rubber coating, and the rubber compound still retains a certain shear load. At this time, adding the second fluororubber raw rubber and continuing to mix for 60–120 seconds allows it to be introduced before the front dispersion state has significantly loosened. Preferably, a narrower window of T / T1 of 0.88–0.91 and a rubber compound temperature of 94–100°C is used, making the front wetting degree, thermal softening degree, and remaining mixing load more concentrated.
[0030] The second fluororubber raw rubber has a higher Mooney viscosity, and its addition raises the mixing load again. The first fluororubber raw rubber, which has already been spread, first contacts and coats the surface of the second fluororubber raw rubber. The already formed front-end filler dispersion continues to transmit shear and tension, causing the high Mooney rubber block to repeatedly widen, fold, and split. The two raw rubbers gradually form a continuous matrix, the front-end filler is redistributed with the rubber compound flow, and the residual agglomerates are further affected. In this stage, the second fluororubber raw rubber adjusts the matrix viscosity and re-establishes the mixing load required for subsequent silica dispersion, laying the foundation for the rubber compound to achieve both injection flowability and shape retention.
[0031] When the second fluororubber raw rubber is added too early, the front-end powder is not yet fully coated, and the high Mooney rubber lumps are prone to forming localized high-load zones together with unwetted agglomerates. When added too late, the first fluororubber raw rubber undergoes deeper thermal softening, weakening the shear transmission capacity of the front-end filler dispersion, and the high Mooney rubber lumps are more likely to remain as strips or small clumps. At the same temperature, different loading states may correspond to different torque reduction processes; at the same torque ratio, the rubber compound may also be in a colder or hotter state. By simultaneously limiting T / T1 and temperature, and keeping the rotor speed and top bolt pressure settings constant during the judgment period, the change in torque ratio can be made to mainly come from the state of the rubber compound in this batch, thereby improving the comparability of the second fluororubber raw rubber addition points.
[0032] After the two raw rubbers are further mixed for 60–120 seconds, the silica is added in two batches. The first batch of silica accounts for 55%–70% of the total silica. After the first batch of silica is added, the mixture is mixed for 30–60 seconds, and then the remaining silica is added. The first batch of silica receives the higher mixing load formed after the addition of the second fluororubber raw rubber and completes the main wetting first. Adding the second batch after a period of mixing reduces the instantaneous increase in powder volume fraction and torque, allowing the later-added silica to enter the shear zone along with the already formed continuous phase of the rubber compound. This arrangement ensures that the mixing load re-established after the addition of the second fluororubber raw rubber continues to act on the reinforcing filler dispersion stage, while reducing powder inclusion, agglomeration, and localized overheating caused by adding powder all at once.
[0033] After adding the second batch of silica, continue mixing for 30–60 seconds, then add fluorowax and carnauba wax. When the rubber compound temperature reaches 105–115°C, add polyethylene wax and continue mixing for another 30–60 seconds, then discharge the compound at 115–125°C. The waxes are added after the fillers are largely dispersed, ensuring the initial mixing load is maintained to break up agglomerates. The polyethylene wax softens and disperses at the specified temperature, working with the fluorowax and carnauba wax to reduce flow resistance and adhesion of the compound to metal surfaces. This preserves the dispersed filler state formed in the initial stage, establishes the lubrication conditions required for injection molding before discharge, and reduces powder inclusions, insufficient local reinforcement, and abnormal flash caused by premature lubrication.
[0034] After the discharged masterbatch is sheeted and cooled to below 40°C, bisphenol AF is added first, and then benzyltriphenylphosphonium chloride is added after dispersion, under conditions of 35-50°C on the open mill and a compound temperature not exceeding 60°C. After both are added, the mixture is passed through a thin mill 5-6 times and sheeted. The compound is then sealed and left to stand at 20-30°C for 16-24 hours. The prior dispersion of bisphenol AF in the masterbatch before the introduction of the accelerator reduces the probability of simultaneous contact of the two at locally high concentrations; the vulcanization system avoids the high-temperature mixing stage, also reducing localized pre-reactions caused by mechanical heat generation. The calendering, splitting, and stacking during the thin-pass process further homogenize the vulcanization system, while the sealed standing allows the internal stress of the compound to gradually relax and the vulcanized components to become more balanced.
[0035] During subsequent vulcanization, active magnesium oxide and calcium hydroxide provide the alkaline conditions required for bisphenol vulcanization and absorb the acidic substances produced in the reaction. Benzyltriphenylphosphonium chloride promotes the crosslinking reaction between bisphenol AF and fluororubber. The acid scavenger and filler have already been dispersed in the preceding stage, and bisphenol AF and the accelerator are sequentially homogenized at low temperatures, which reduces the difference in vulcanization rate across the rubber compound, thus balancing processing safety and the uniformity of the crosslinking network.
[0036] The above preparation process establishes a continuous state transfer relationship. The first fluororubber raw material and the upstream filler first form a transitional state that can be identified by both the torque curve and temperature. The second fluororubber raw material is added in this state and a new mixing load is established. Silica is then dispersed in batches using this mixing load. Waxes are used to adjust the downstream flow after the filler dispersion is complete. Finally, the vulcanization system is uniformly dispersed under low-temperature conditions. The process control object shifts from a preset mixing time or a single temperature to the actual state of the batch of rubber compound. This allows fluctuations in raw materials and thermal history to be absorbed through changes in the timing of material addition, and integrates raw rubber blending, filler dispersion, injection flow, scorch safety, and post-vulcanization performance within the same process.
[0037] All components listed below are based on a total of 100 parts by weight of the first and second fluororubber raw rubbers, wherein the first fluororubber raw rubber comprises 78-82 parts by weight and the second fluororubber raw rubber comprises 18-22 parts by weight. The embodiments also commonly employ 6 parts by weight of activated magnesium oxide, 6 parts by weight of calcium hydroxide, 20 parts by weight of N990 carbon black, 10 parts by weight of calcium silicate, 5 parts by weight of barium sulfate, 10 parts by weight of silica, 1 part by weight of fluorowax, 1.5 parts by weight of carnauba wax, 0.8 parts by weight of polyethylene wax, 2.17 parts by weight of bisphenol AF, and 0.5 parts by weight of benzyltriphenylphosphonium chloride.
[0038]
[0039] Example 1: The mixing chamber of the internal mixer was pre-cooled to 60°C, and the rotor speed was set to 40 r / min and the top plug pressure to 0.45 MPa. 80 parts by mass of first fluororubber raw material with a Mooney viscosity of 25 were added and masticated for 75 seconds. Then, activated magnesium oxide, calcium hydroxide, N990 carbon black, calcium silicate, and barium sulfate were added, and the top plug was closed after the feeding was completed. After the pressure stabilized, the torque was recorded, and the first local maximum value of the processed curve was recorded as T1. Keeping the rotor speed and top plug pressure settings constant, during the torque drop phase after T1, when T / T1 was 0.895 and the compound temperature was 97°C, 20 parts by mass of second fluororubber raw material with a Mooney viscosity of 70 were added, and mixing continued for 90 seconds.
[0040] Add 6.2 parts by weight of silica as the first batch of silica, and mix for 45 seconds. Then add the remaining 3.8 parts by weight of silica. Continue mixing for another 45 seconds, and then add fluorowax and carnauba wax. When the rubber compound temperature reaches 110°C, add polyethylene wax and continue mixing for 45 seconds. When the rubber compound temperature reaches 120°C, discharge the rubber. The masterbatch is sheeted through a two-roll mill and cooled to below 40°C. Then, under conditions of a roll temperature of 42°C and a maximum rubber compound temperature of 56°C, first add bisphenol AF, disperse evenly, and then add benzyltriphenylphosphonium chloride. Pass through the mill 6 times and then sheet. The resulting compound is sealed and left to stand at 25°C for 24 hours.
[0041] Examples 2-5: Examples 2-5 were performed according to the basic operation of Example 1. The raw rubber parameters are shown in Table 1, and the state triggering conditions, the batch ratio of silica, and subsequent process parameters are shown in Tables 2 and 3. Each time, the rotor speed of 40 r / min and the top bolt pressure of 0.45 MPa were kept constant from the start of torque recording until the addition of the second fluororubber raw rubber.
[0042]
[0043]
[0044] Comparative Examples 1-9 all used the same formulation, raw material grades, and equipment as Example 1. The process changes for Comparative Examples 1-6 are shown in Table 5; except for the corresponding changes, the remaining operations were the same as in Example 1. The control methods for Comparative Examples 7-9 are shown in Table 5, and their initial mixing chamber temperature, actual feeding time, torque ratio during feeding, and rubber compound temperature are shown in Table 8. Operations not listed are the same as in Example 1.
[0045]
[0046] (1) The images of the rubber compound were analyzed according to ISO 11345. The filler dispersion was represented by a grade of 0 to 10. The larger the value, the fewer visible agglomerates. The strain was scanned at 100℃ and 1Hz using a rubber processing analyzer. The difference between the storage modulus at 0.28% strain and the storage modulus at 100% strain was expressed as ΔG′. The smaller ΔG′, the lower the degree of agglomeration of the filler network.
[0047] (2) The Mooney viscosity of the compound rubber was determined by ML(1+4) at 100℃, and the Mooney scorch time t5 was determined by ISO 289-2 at 121℃. The Mooney viscosity of raw rubber and the Mooney viscosity of the compound rubber were tested at different temperatures and rotor times, and the two were not directly converted.
[0048] (3) The injection flowability was evaluated using a spiral flow channel mold with a cross-sectional dimension of 4mm×6mm. The injection molding machine barrel temperature was 90℃, the nozzle temperature was 100℃, the mold temperature was 175℃, and the injection pressure was 90MPa. The spiral flow length when the rubber material reached the stable leading edge was recorded. 500 samples with thin-walled sealing lips were continuously injected in each batch. Any of the following conditions, such as insufficient glue, weld line cracking, abnormal flash, or surface powder inclusion, was counted as a defective part. The defect rate was calculated as the percentage of defective parts out of 500 samples.
[0049] (4) The vulcanization characteristics were determined using a rotorless vulcanizer at 177℃ in accordance with ISO 6502-3, and the positive vulcanization time t was recorded. 90The difference between the maximum and minimum torque, ΔM. Mechanical properties were determined by first vulcanizing the specimens at 177℃ for 10 min, then performing a second-stage vulcanization at 230℃ for 16 h; tensile properties were determined according to ISO 37, and Shore A hardness was determined according to ISO 48-4. Compression set was determined according to ISO 815-1, with a compression of 25%, and the specimens were held at 200℃ for 70 h.
[0050] Examples 1-5 and Comparative Examples 1-6 each prepared three independent batches. Comparative Examples 7-9 each prepared one batch according to the three initial mixing chamber temperatures listed in Table 8. Tables 6 and 7 list the average values of the three batches for each sample, and the injection molding defect rate is statistically calculated based on a total of 1500 samples from the three batches.
[0051]
[0052] In Example 1 and Comparative Examples 7-9, three batches were set up, with initial mixing chamber temperatures of 52℃, 60℃, and 68℃ respectively. In Example 1, the material was added when both T / T1 and temperature entered the specified range; in Comparative Example 7, a fixed time was used; in Comparative Example 8, only the temperature criterion was used; and in Comparative Example 9, only the torque ratio criterion was used. The results are shown in Table 8.
[0053]
[0054] Tables 6 and 7 show that the filler dispersion in Examples 1-5 was 8.6-9.3, ΔG′ was 138-169 kPa, Mooney viscosity of the compound was 56-61, spiral flow length was 332-354 mm, Mooney scorch time was not less than 29.2 min, and injection molding defect rate was not higher than 2.4%; the tensile strength after vulcanization was not less than 15.9 MPa, and the compression set was not higher than 19.1%. Examples 2 and 3, using endpoint conditions of T / T1, feeding temperature, mixing time, and batch ratio of silica, respectively, still maintained stable overall performance of the resulting compounds. Examples 1, 4, and 5, using the preferred state window, achieved a filler dispersion of 9.0-9.3 and a reduction in injection molding defect rate to 1.2%-1.7%, indicating that the above state window and its preferred range can achieve dispersion, flow, and scorch performance suitable for injection molding.
[0055] In Comparative Example 1, two types of raw rubber were added simultaneously. The high Mooney rubber block and powder were mixed together. The preferential coating of the powder by the first fluororubber raw rubber was disrupted, the filler dispersion decreased to grade 7.2, and the spiral flow length decreased to 288 mm. In Comparative Example 2, the second fluororubber raw rubber was added earlier. In Comparative Example 3, it was added after the torque had significantly decreased and the rubber temperature had increased. Both examples showed an increase in ΔG′, a decrease in flow length, and an increase in defect rate. Compared to Comparative Example 1, Example 1 showed a reduction in ΔG′ of approximately 46.5%, an increase in spiral flow length of approximately 22.9%, a reduction in injection molding defect rate of approximately 84.6%, an increase in tensile strength of approximately 16.8%, and a reduction in compression set of approximately 26.1%. With the same formulation, multiple properties improved simultaneously, indicating that the timing of rubber mixing has a continuous impact on raw rubber fusion, filler dispersion, mold filling, and post-vulcanization properties. The improvements achieved exceed those obtained by directly using two Mooney viscosity raw rubbers for conventional viscosity adjustment.
[0056] In Comparative Example 4, all silica was added at once, resulting in concentrated instantaneous powder loading, a filler dispersion grade of 7.7, and an injection molding defect rate of 5.0%. In Comparative Example 5, all waxes were added in advance, reducing the Mooney viscosity of the compound to 53 and achieving a spiral flow length of 362 mm, higher than the 354 mm in Example 1; however, its filler dispersion grade was only 7.0, the defect rate increased to 6.6%, the tensile strength decreased to 13.5 MPa, and the compression set increased to 26.5%. These results indicate that a longer spiral flow distance may still be accompanied by poor filler dispersion and a higher molding defect rate, and advance lubrication weakens the initial dispersion load. Example 1 achieved a slightly lower flow length but simultaneously obtained a dispersion grade of 9.3, a defect rate of 1.2%, and good post-curing performance. Adding silica in batches and placing waxes in the later stages can improve flow while maintaining sufficient filler dispersion, thus coordinating spiral flow length, molding defect rate, and post-curing performance.
[0057] Comparative Example 6, with the addition of the vulcanization system during the high-temperature mixing stage, still achieved a filler dispersion of 8.9, similar to the example. However, the Mooney scorch time was shortened to 16.8 min, the spiral flow length decreased to 273 mm, and the defect rate reached 9.4%. While the dispersion of Comparative Example 6 was close to that of the example, its processing safety and injection molding performance significantly declined, indicating that filler dispersion and the timing of vulcanization system addition acted at different stages. Even with good dispersion, the injection molding window can be lost if local pre-reaction interference occurs later. Adding bisphenol AF and benzyltriphenylphosphonium chloride sequentially during the low-temperature open mixing stage can reduce premature thickening at high temperatures, allowing the dispersion advantages gained in the earlier stages to continue to be transferred to the injection molding and vulcanization stages.
[0058] As shown in Table 8, the dual-state criteria have a complementary effect. When the initial temperature of the mixing chamber changes from 52℃ to 68℃, Example 1 adjusts the feeding time accordingly to 214-266s. All three batches of feeding fall within the specified torque ratio and temperature range, and the coefficient of variation of the spiral flow length is approximately 0.75%. Comparative Example 7 has a fixed feeding time of 240s, with a coefficient of variation of approximately 13.0%; Comparative Example 8 is triggered only at 97℃, with a coefficient of variation of approximately 9.8%; and Comparative Example 9 is triggered only at T / T1 of 0.895, with a coefficient of variation of approximately 10.4%.
[0059] All three comparison methods approached the optimal feeding point at an initial temperature of 60℃. After changes in initial thermal conditions, deviations occurred between a single temperature and the load reduction process, and a single torque ratio also corresponded to a colder or hotter rubber compound state. T / T1 was used to track the relative mixing process, and temperature was used to correct the thermal state. With both criteria constraining the process, changes in the initial temperature of the mixing chamber could be compensated for by adjusting the timing of the second fluororubber raw rubber addition, significantly reducing the fluctuation in spiral flow length under different initial thermal states. Example 1 demonstrated better process adaptability to changes in initial thermal state than fixed-time control or any single criterion.
[0060] Combining the results in Tables 6 to 8, a continuous interaction relationship is formed at each stage. The dual-state criterion first controls batch differences before the introduction of the second fluororubber raw rubber; the batch addition of silica and the subsequent placement of waxes ensure that the mixing load is first used for dispersion and then for establishing effective flow; the vulcanization system is added sequentially at low temperatures, thus preserving the dispersion results of the previous stage and maintaining scorch safety.
[0061] Comparative Example 5 achieved a longer single-flow distance, but with a higher defect rate and worse post-curing performance; Comparative Example 6 maintained high dispersion, but significantly lost scorch safety; the single-state criterion, while approaching a suitable point within a batch, still exhibited significant fluctuations in response to changes in thermal history. These results indicate that simply reducing viscosity, increasing filler dispersion, or relying on a single process parameter alone is insufficient to simultaneously achieve stable mold filling, a longer scorch time, and good post-curing performance. When the process stages are sequentially connected as described above, the examples simultaneously achieve a spiral flow length of 332–354 mm, an injection molding defect rate of no more than 2.4%, a Mooney scorch time of no less than 29.2 min, and maintain a tensile strength above 15.9 MPa and a compressive settling below 19.1%, demonstrating synergistic effects between the steps.
[0062] The above embodiments describe specific implementations of the present invention. Within the scope of the technical concept and claims of the present invention, equipment specifications, raw material grades, and routine operating details can be adjusted equivalently.
Claims
1. A method for preparing a fluororubber compound for injection molding, characterized in that, Includes the following steps: (1) Pre-cool the mixing chamber of the internal mixer to below 70°C, put the raw rubber of the first fluororubber into the internal mixer for plasticizing, and then add active magnesium oxide, calcium hydroxide, N990 carbon black, calcium silicate and barium sulfate for mixing; (2) After the above components are fed and the top bolt is closed, the mixing torque is recorded after the pressure of the top bolt reaches the set value. The first peak torque recorded is recorded as T1. During the torque drop phase after T1, when the ratio of the real-time torque T to T1 is 0.85 to 0.93 and the rubber temperature is 90 to 105°C, the second fluororubber raw rubber is added and mixing continues. From the start of recording the mixing torque until the addition of the second fluororubber raw rubber, the rotor speed setting value and the top bolt pressure setting value of the internal mixer remain unchanged. (3) After the second batch of fluororubber raw rubber is added and mixed, silica is added in two batches. After the first batch of silica is added and mixed, the second batch of silica is added. (4) After the second batch of silica is added and mixed, fluorinated wax and carnauba wax are added; when the temperature of the rubber compound reaches 105-115℃, polyethylene wax is added, and mixing continues. When the temperature of the rubber compound reaches 115-125℃, the rubber is discharged to obtain the masterbatch. (5) The masterbatch is sheeted and cooled to below 40°C, and then placed in a two-roll mill. Bisphenol AF and benzyltriphenylphosphonium chloride are added sequentially under the condition that the roller temperature of the two-roll mill is 35-50°C and the temperature of the rubber compound is not higher than 60°C. After mixing and sheeting, fluororubber compound for injection molding is obtained. Both the first and second fluororubber raw rubbers are suitable for bisphenol vulcanization systems. The Mooney viscosity of the first fluororubber raw rubber is 20-30, and the Mooney viscosity of the second fluororubber raw rubber is 65-75. The Mooney viscosity of both is expressed in ML(1+10)121℃.
2. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, Based on a total usage of 100 parts by weight of the first and second fluororubber raw rubbers, the usage of each component is as follows: The mixture consists of 78-82 parts by weight of first-grade fluororubber raw rubber, 18-22 parts by weight of second-grade fluororubber raw rubber, 6 parts by weight of activated magnesium oxide, 6 parts by weight of calcium hydroxide, 20 parts by weight of N990 carbon black, 10 parts by weight of calcium silicate, 5 parts by weight of barium sulfate, 10 parts by weight of silica, 1 part by weight of fluorinated wax, 1.5 parts by weight of carnauba wax, 0.8 parts by weight of polyethylene wax, 2.17 parts by weight of bisphenol AF, and 0.5 parts by weight of benzyltriphenylphosphonium chloride.
3. A method for preparing a fluororubber compound for injection molding according to claim 1 or 2, characterized in that, Before being fed into the internal mixer, neither the first nor the second fluororubber raw rubber was premixed with bisphenol AF and benzyltriphenylphosphonium chloride.
4. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, When adding the second fluororubber raw rubber, the ratio of real-time torque T to T1 is 0.88 to 0.91, and the rubber compound temperature is 94 to 100℃.
5. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, The first batch of fluororubber raw rubber is masticated for 60-90 seconds; after the second batch of fluororubber raw rubber is added, continue mixing for 60-120 seconds, and then add the first batch of silica.
6. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, The first batch of silica accounts for 55% to 70% of the total silica usage, and the second batch of silica is the remainder. After the first batch of silica is added, continue mixing for 30 to 60 seconds before adding the second batch of silica.
7. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, After the second batch of silica is added, continue mixing for 30-60 seconds, then add fluorowax and carnauba wax; after the polyethylene wax is added, continue mixing for 30-60 seconds, and discharge the rubber compound when the temperature reaches 115-125℃.
8. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, After adding bisphenol AF and benzyltriphenylphosphonium chloride, the rubber compound is passed through a thin tube 5-6 times and then sheeted out.
9. The method for preparing a fluororubber compound for injection molding according to claim 1, characterized in that, After sheeting, the fluororubber compound for injection molding is sealed and left to stand at 20-30°C for 16-24 hours.
10. A fluororubber compound for injection molding, characterized in that, Based on a total of 100 parts by weight of first fluororubber raw material and second fluororubber raw material, the raw materials for its preparation include: The mixture consists of 78-82 parts by weight of first-grade fluororubber raw rubber, 18-22 parts by weight of second-grade fluororubber raw rubber, 6 parts by weight of activated magnesium oxide, 6 parts by weight of calcium hydroxide, 20 parts by weight of N990 carbon black, 10 parts by weight of calcium silicate, 5 parts by weight of barium sulfate, 10 parts by weight of silica, 1 part by weight of fluorinated wax, 1.5 parts by weight of carnauba wax, 0.8 parts by weight of polyethylene wax, 2.17 parts by weight of bisphenol AF, and 0.5 parts by weight of benzyltriphenylphosphonium chloride. Both the first and second fluororubber raw rubbers are suitable for bisphenol vulcanization systems. The Mooney viscosity of the first fluororubber raw rubber is 20-30, and the Mooney viscosity of the second fluororubber raw rubber is 65-75. The Mooney viscosity of both is expressed in ML(1+10)121℃.
Citation Information
Patent Citations
Fluororubber rubber compound and preparation method thereof
CN102875937A
Fluororubber compound and preparation method thereof
CN104356559A